Effects of Functional Electrical Stimulation on Gait Recovery Post-Neurological Injury during Inpatient Rehabilitation. Issue 2 (October 2014) - Lairamore, Chad I.; Garrison, Mark K.; Bourgeon, Laetitia; Mennemeier, Mark
This stage 2 trial investigated the therapeutic effect of single channel, peroneal functional electrical stimulation (FES) for improving gait and muscle activity in people with neurological injuries who were enrolled in an inpatient rehabilitation program. Twenty-six patients (16 male; M age = 51.3 yr., SD = 16.2; 2–33 days post-injury) completed the study. Participants were randomly assigned to an experimental group ( n = 13) or control group ( n = 13). The experimental group received FES and the control group received sensory stimulation during 45-min. gait training sessions three times a week for the duration of their stay in a rehabilitation facility (average of four sessions for both groups). Changes in gait speed, tibialis anterior muscle electromyography (EMG), and FIM™ locomotion scores were compared between groups. No significant differences were found, as both groups demonstrated similar improvements. The current results with this small sample suggest a low dose of gait training with single channel FES did not augment gait nor EMG activity beyond gait training with sensory stimulation; therefore, clinicians will likely be better served using a larger dose of FES or multichannel FES in this clinical population.